Impact Analysis of Environmental Law Policy on Cirebon Coastal Communities in Climate Change Adaptation - MAHARDEKA, Adelia Putri; WULANDARI, Siwi; MAGFIRRO, Rosiana (Journal of Political And Legal Sovereignty, 2025)
Purpose:Cirebon's coastal communities face intensifying climate change impacts, such as sea level rise, coastal abrasion, and natural disasters, which threaten their socio-economic resilience. However, the implementation of this policy still faces various challenges, including overlapping regulations, weak law enforcement, and lack of community participation in the policy formulation process.Methodology:This research uses a qualitative approach with a case study method to evaluate the effectiveness of environmental law policies in supporting the social adaptation of Cirebon's coastal communities. Data were collected through in-depth interviews with affected communities, government officials, and policy experts, as well as analysis of related legal documents.Findings:The results showed a gap between policies and factual conditions in the field, especially in inter-agency coordination, resource allocation, and community access to environmental justice.Implication:This study emphasizes the need for environmental law policy reform that is more adaptive, ecologically just, and oriented towards empowering coastal communities in the face of climate change.